Valoración clínica y cefalométrica del aparato de distracción de García para el tratamiento de la mordida abierta anterior en pacientes atendidos en la facultad de odontología, universidad de Antioquia, Medellín (2009)
ABSTRACT: This study aims to determine radiographic and clinical changes obtained with the Garcia’s distractor appliance® and its craniofacial, dental and facial cosmetic effects in patients with anterior open bite. Methods: a prospective clinical quasi-experimental study in 9 subjects, 2 men and 7 women, 7 of them in a phase of active growth with an average age of 11.7 years and 2 adults with an average age of 30 years, in which cephalic radiographs were obtained at the beginning, third and sixth month of treatment. The clinical effect was assessed by measuring monthly the overbite and overjet with a digital gauge Discover®. In the statistical analysis, descriptive measures were obtained using ANOVA test for repeated measurements to determine changes over time, with a level of significance of 0.05. Results: the radiographic findings showed an increase in the goniac angle in the growing patients; also, an increase in the overbite and a decrease in the overjet were observed, these changes are explained by the intrusion of the upper molars and retro inclination of the upper and lower incisors; facially, there was a decrease in the angle of convexity in the soft tissues. Conclusions: the Garcia’s distractor appliance® used for a period of six month in growing patients improved the open bite by intrusion of upper molars and retro inclination of upper and lower incisors.